2015
DOI: 10.1002/j.0022-0337.2015.79.11.tb06024.x
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Education in U.S. Dental Hygiene Programs: A National Survey

Abstract: Although there are many beneits of interprofessional health care, no previous research has sought to deine the status of interprofessional education (IPE) in U.S. dental hygiene programs. The aims of this study were to assess how these programs engage in IPE, the challenges they encounter, and the value they place on IPE. Additionally, the study explored how program characteristics are related to IPE. Data were collected with a web-based survey sent to all 322 U.S. dental hygiene program directors (response ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Theile and colleagues identified how dental hygienists can embrace their role in interprofessional practice, not only through traditional practice settings, but also by contributing to oral‐systemic health research and facilitating implementation science; all of which would require knowledge of different delivery settings. Although frameworks to implement an interprofessional curriculum for medical, nursing, and dental students exist, given the separation of dental and health care in Canada—in terms of organization, financing, and delivery—there may be little drive for professions to establish shared learning environments…”
Section: Discussionmentioning
confidence: 99%
“…Theile and colleagues identified how dental hygienists can embrace their role in interprofessional practice, not only through traditional practice settings, but also by contributing to oral‐systemic health research and facilitating implementation science; all of which would require knowledge of different delivery settings. Although frameworks to implement an interprofessional curriculum for medical, nursing, and dental students exist, given the separation of dental and health care in Canada—in terms of organization, financing, and delivery—there may be little drive for professions to establish shared learning environments…”
Section: Discussionmentioning
confidence: 99%
“…The investigators of the 2014 study made two revisions to the original dental school survey. They changed the program characteristics questions to be appropriate for dental hygiene program directors, and they replaced the IPE‐related predoctoral dental CODA standard numbers in the dental school survey with the dental hygiene CODA standards that were indirectly relevant to IPE 21 . In the 2017 study, we made one change to the dental hygiene survey used in 2014.…”
Section: Methodsmentioning
confidence: 99%
“…In consideration of this situation, it was not surprising that the Commission on Dental Accreditation (CODA) Accreditation Standards for Dental Hygiene Education Programs revised Standard 2–15 in August 2016 to explicitly include IPE. This standard now states that “Graduates must be competent in communicating and collaborating with other members of the health care team to support comprehensive patient care.” 20 Furgeson et al surveyed dental hygiene program directors regarding their IPE‐related efforts and attitudes in 2014, when only implicit references to IPE were made in the CODA standards, 21 but no prior study has assessed whether educational efforts and attitudes changed as a consequence of the CODA standard changes in August 2016.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The logistics of then trying to introduce IPE, for often a large number of students with complex curriculum timetables can be challenging, particularly if not all staff appreciate the value of IPE. It has been found that schedule coordination (92%) and curriculum overload (76%) were issues when implementing IPE within a dental hygiene curriculm 15 and that support from educational leaders and administrators is essential 7 . There is also thought that pre-registration students should be focussing on developing their uniprofessional skills and professional identity prior to learning collaboratively as part of IPE.…”
Section: Ipe Pre-registration or Post-registration?mentioning
confidence: 99%